Determinants Of Interest In Becoming A Public Accountant - MARSYAF, Marsyaf (PT Keberlanjutan Strategis Indonesia, 2021)
This study aims to examine the effect of self-motivation, perceptions of the public accounting profession, financial rewards, and professional recognition on interest in becoming a public accountant. The population in this study were students of the accounting study program at Mercu Buana University. Sampling as many as 81 using purposive sampling technique. The research data collection technique was done through a questionnaire. The data analysis method used in this research is multiple linear regression analysis. The results showed that self-motivation had a positive and significant effect on interest in becoming a public accountant, while perceptions of the public accounting profession, financial rewards, and professional recognition had no significant effect on interest in becoming a public accountant.